Penerapan Metode Economic Order Quantity pada Sistem Informasi Persediaan Barang Perusahaan Otomotif - Pujiastuti, Pujiastuti; Ariyani, Lusi (Teknik Informatika Universitas Pamulang, 2021)
Trading companies, such as automotive product sales companies, of course prepare stock of sales products in the warehouse section. The warehouse department often has difficulty in the process of finding goods. The placement of inventory positions that are not well organized is one of the causes of the warehouse section having difficulty finding goods. The condition of the goods in the warehouse is often placed in an unfavorable position so that the search for goods takes time. This incident is very ineffective if the goods are needed at the time of the sale of goods. This incident also affects the time of making inventory reports. This research was conducted to help the activities of product data processing in the warehouse to be better. Development of a web-based inventory information system using the Economic Order Quantity method. How this method works can provide information about the number of requests is known, constant, independent. Inventory information is available according to customer orders, there are no price discounts and avoid stock outs if there is an order for goods but the goods are not available.